A Tale of Two Cities: John Henry Newman and the Church of the Catacombs - Meyer, Wendel W. (The journal of ecclesiastical history, 2010)
John Henry Newman made two formative trips to Rome, the first as an Anglican priest in the early spring of 1833 when he spent five weeks in the Eternal City accompanied by his friend and colleague Hurrell Froude. The second trip was made shortly after he converted to Roman Catholicism in 1846. On both these journeys, Newman visited the Roman catacombs, which were certainly part of the standard tour of the day but which had become in the nineteenth century sites that were enveloped in considerable ecclesiastical and theological polemical debate. Looking at Newman's reactions to these sites, at these two very important junctures of his life and career, gives a very provocative and enlightening glimpse into the inner workings of his mind and heart. On a different but equally interesting historical plane, such an investigative lens highlights the significant number of people who were part of Newman's life during this period and who were devotionally drawn to these primitive burial sites.